I CAN CHANGE THE WORLD... : WITH THE CHOICE OF MY FOOD - Chan, Ronald; Yee, Wearn (Singapore : WS Education, 2022)
He is Mr Food Snapper on weekdays, a food enthusiast who shares photographs of his favourite food on social media ... and Mr Food Saver on weekends, our neighbourhood eco-warrior on the prowl for people wasting precious food. Follow Mr Food Saver as he explains how one little action from us could make a huge difference to the sustainability of our world.Every book in the I Can Change the World... collection contains a creative story that highlights the importance of individual action on environmental sustainability. Through engaging narratives and full-colour illustrations, the I'm a Little Scientist series introduces children to the exciting and ever-advancing world of science.
Includes QR code, scan it to access bonus resources!
Keywords: Food waste -- Readers -- Fiction; Sustainable living -- Juvenile fiction